Mahātmā Gāndhi : addēhattinṯe jīvitattēyuṃ pṟavrttiyēyuṃ kuṟiccuḷḷa upanyāsaṅṅaḷuṃ abhipṟāyaṅṅaḷuṃ - Radhakrishnan, S. (Sarvepalli), 1888-1975 (SAMP early 20th-century Indian books project, 1946)
On Mahatma Gandhi's life and work, essays presented to him on his birthday on 10/2/1939 by Sarvepalli Radhakrishnan.